Rutaceae: conservation at Eka Karya Bali Botanic Garden and its in vitro antifungal activity screening - I Putu Agus Hendra Wibawa; Arrohmatus Syafaqoh Li'aini; Putri Sri Andila; Frelyta Ainuz Zahro' (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2021)
Several species of Rutaceae have been widely used and commercialized in all regions in Indonesia. Some species of Rutaceae are consumed as fresh fruit and traditional medicine for various kinds of diseases, as well as to add aroma to various Indonesian culinary. Since 1959, Eka Karya Bali Botanic Garden (Eka Karya BBG) has successfully collected dozens of Rutaceae species with unknown potential. In addition to reporting the conservation of Rutaceae in Eka Karya BBG, this study aimed to screen the antifungal activity of Rutaceae methanolic extract toward Aspergillus niger, Cladosporium sp., and Fusarium solani. Leaves of 13 species of Rutaceae (Boenninghausenia sp., Citrus aurantifolia, C. maxima, C. medica, Clausena sp., Melicope sp., Micromelum sp., Murraya paniculata, Toddalia sp., Zanthoxylum sp., Z. alatum, Z. limonella, and Z. ovalifolium) were collected, cleaned, air-dried, soaked in methanol for three days, then evaporated using a rotary evaporator to obtain the plant crude extract. The in vitro inhibitory assay was conducted by the diffusion method. As a result, only C. medica, Clausena sp., and Z. limonella exhibited antifungal activity against those tested fungi. Their antifungal activity increased on day 2 post-treatment but slowly decreased on day 3. Thus, the result of this experiment can be used as preliminary data to researchRutaceae plant extracts as an alternative method to control pathogenic fungi. However, further research is needed to maintain and increase its inhibitory effect.